2022
DOI: 10.1155/2022/8011988
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Alleviates the Progression of Breast Cancer-Related Depression via Inhibiting the Pyroptosis and Promoting the Immune Response

Abstract: Background. Breast cancer-related depression (BCRD) seriously inhibits the life quality of patients with breast cancer. The Xiaoyao Kangai Jieyu Formula is known to inhibit the progression of depression. However, the detailed function of the Xiaoyao Kangai Jieyu Formula in BCRD remains unclear. Methods. Network pharmacology was constructed to assess the downstream target of the Xiaoyao Kangai Jieyu Formula in BCRD. In addition, the tail suspension test, sucrose preference test, and forced swimming test were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…57 Among the SBF flavonoids, quercetin has been reported to have anti-depression ability. For example, it was reported that quercetin relieved the depressive-like symptoms in LPS-induced mice via the regulation of the PI3K/AKT/NF-κB and CREB/BDNF pathways, 58 restored breast cancer-related depression by suppressing cell pyroptosis and promoting the immune response, 59 as well as regulated the inflammatory, oxidative stress and 5-HT levels in vivo . 60 Meanwhile, isorhamnetin and kaempferol have functions in the treatment of brain defects.…”
Section: Discussionmentioning
confidence: 99%
“…57 Among the SBF flavonoids, quercetin has been reported to have anti-depression ability. For example, it was reported that quercetin relieved the depressive-like symptoms in LPS-induced mice via the regulation of the PI3K/AKT/NF-κB and CREB/BDNF pathways, 58 restored breast cancer-related depression by suppressing cell pyroptosis and promoting the immune response, 59 as well as regulated the inflammatory, oxidative stress and 5-HT levels in vivo . 60 Meanwhile, isorhamnetin and kaempferol have functions in the treatment of brain defects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the medicines mentioned in the previous section, some potential agents have also been reported to exert roles through other anti-inflammatory mechanisms. Isoliquiritin ( Li, Y. et al, 2021 ), pinocembrin ( Yang et al, 2022 ), pilose antler peptide ( Hu et al, 2022 ), quercetin ( Zhu et al, 2022 ), etc. ameliorated depression by suppressing pyroptosis in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, quercetin has not been reported to possess anti-tumor effects through the regulation of pyroptosis. However, it has been investigated that the specific role of quercetin in breast cancer-related depression (BCRD), in which the inhibition of pyroptosis and promotion of immune response are the main mechanisms for effectively mitigating the progression of BCRD ( Zhu et al, 2022 ). In this study, quercetin partially reversed the pyroptosis on LPS-cultured 4T1 cells in vitro , as evidenced markedly by upregulating the card structural domain, NLR family pyrin structural domain (NLRP3), and Caspase-1.…”
Section: Therapeutic Mechanisms Of Quercetin Targeting Non-apoptotic ...mentioning
confidence: 99%